2011
DOI: 10.1016/j.trsl.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA, a new paradigm for understanding immunoregulation, inflammation, and autoimmune diseases

Abstract: microRNAs (miRNAs) are newly discovered, small, non-coding ribonucleic acids (RNAs) that play critical roles in the regulation of host genome expression at the post-transcriptional level. During last two decades, miRNAs have emerged as key regulators of various biological processes including immune cell lineage commitment, differentiation, maturation, and maintenance of immune homeostasis and normal function. Thus, it is not surprising that dysregulated miRNA expression patterns have now been documented in a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
312
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(332 citation statements)
references
References 181 publications
11
312
0
9
Order By: Relevance
“…In some inflammatory disorders, studies have suggested that prominent up-regulation of miRNAs, such as miR21, is specifically involved in modulating TLR associated NFÎșB signaling networks activated by the pathological microenvironment (Kalla et al, 2015). Conceivably, miR146a is differentially expressed in various autoimmune diseases including rheumatoid arthritis and multiple sclerosis and its regulation may influence the development or prevention of autoimmunity (Dai and Ahmed, 2011). As exosomes naturally transfer RNA molecules between cells, this property may be useful in gene therapy, in which a vector is used to deliver therapeutic nucleic acids to the patient's target cells.…”
Section: Perspectives and Final Remarksmentioning
confidence: 99%
“…In some inflammatory disorders, studies have suggested that prominent up-regulation of miRNAs, such as miR21, is specifically involved in modulating TLR associated NFÎșB signaling networks activated by the pathological microenvironment (Kalla et al, 2015). Conceivably, miR146a is differentially expressed in various autoimmune diseases including rheumatoid arthritis and multiple sclerosis and its regulation may influence the development or prevention of autoimmunity (Dai and Ahmed, 2011). As exosomes naturally transfer RNA molecules between cells, this property may be useful in gene therapy, in which a vector is used to deliver therapeutic nucleic acids to the patient's target cells.…”
Section: Perspectives and Final Remarksmentioning
confidence: 99%
“…Therefore, not surprisingly, abnormalities in the expression and functioning of miRNAs have been identified as part of the pathogenesis of autoimmune diseases including SLE [Dai and Ahmed, 2011;Shen et al 2012] . Dai and colleagues first reported the identification of six miRNAs whose expression was altered in the peripheral blood mononuclear cells (PBMCs) prepared from patients with SLE, but not patients with idiopathic thrombocytopenic purpura [Dai et al 2007].…”
Section: Epigenetics-related Biomarkersmentioning
confidence: 99%
“…miRNA is estimated to control 30-90% of human genes (4). miRNA has been suggested to either suppress messenger RNA (mRNA) translation or reduce mRNA stability by binding particular regions of mRNA (5).…”
Section: Introductionmentioning
confidence: 99%